Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian di Puskesmas Sentani dan Puskesmas Waena, Provinsi Papua - Ega Riana; Elsye Gunawan; Nur F. Bakrie (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
Patient satisfaction is a level of patient feeling that arises as a result of the performance of health services that their received after compared to the expectation. Pharmaceutical service is a form of direct and responsible service to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the quality of life of patients. This research was conducted at the Sentani Health Center and Waena Health Center in July-August 2020,This study used descriptive survey method, sampling with purposive sampling method. Data will be obtained through questionnaires which distributed to respondents who meet the research inclusion criteria. The results showed that as many as 200 respondents are satisfied with the quality of pharmaceutical services at the Sentani Health Center and the Waena Health Center, for the five consecutive dimensions as follows Reliability with a score of 4.05 and 4.15, Responsiveness with a score of 4.07 and 4.20, Confidence with a score of 4.11 and 4.00, Empathy with a score of 4.07 and 4 .00, and Tangible 4.17 and 4.18, respectively. This means that patients and their families are satisfied with pharmaceutical services at the Sentani and Waena health centers in Jayapura, Papua.Key words: patient satisfaction; pharmaceutical services; Sentani Health Center; Jayapura.